La recuperación de la salud mental de adolescentes y jóvenes con adicciones al alcohol. Una estrategia de educación para la salud con sus redes de apoyo. - Aldeán Ayala, Jorge Ramiro (2014)
The present study titled: THE RECOVERY OF MENTAL HEALTH OF ADOLESCENTS WITH ALCOHOL ADDICTION .A STRATEGY FOR HEALTH EDUCATION WITH YOUR SUPPORT NETWORKS. The overall objective of this research was: To investigate the Mental Health posing teens and youth with addictions to alcohol that are internal to the Recovery Center of Canton Loja. The methodology being used a descriptive study : techniques, tools and procedures necessary to describe the reality of the variables and indicators raised . The instruments used were the Hamilton Anxiety Scale , applied to teenagers and young people with addictions to alcohol that are internal to Recovery Centers to assess the types and levels of anxiety , and the Hamilton Rating Scale for Depression, applied to adolescents and young people to assess the intensity of depression . From the results of the Test of Hamilton Anxiety applied to adolescents and youth with addictions to alcohol is concluded that: 36% have anxiety somatic type with light intensity, 25% with medium intensity somatic anxiety, 19% somatic anxiety high intensity, 14% absent somatic anxiety and somatic anxiety 6% maximum intensity. Regarding Psychic Anxiety is concluded that: the 36 % present with light intensity psychic anxiety, 21% with medium intensity psychic anxiety, 19% with high intensity psychic anxiety, 15% maximum intensity psychic anxiety and 10% psychic anxiety absent. As follows from the data obtained from the Hamilton Rating Scale for assessing the intensity of depression: 38% of adolescents and young people observed valuation obtained between 14 to 18 points Moderate Depression, 26% obtained an appraisal from 8 -18 points Low Mild Depression, 14% higher than 23 points depression very Severe, 12% between 19-22 points Severe Depression, 10% between 0-7 points not depressed. I propose a strategy of health education with their support networks, and to work the levels of anxiety and depression through a series of training activities in order to recover the Mental Health, initially in the family and then with networks support collective where teens and young adults with alcohol addiction are.